The literary performative structure and Iser’s theory of aesthetic effect - Borba, Maria Antonieta Jordão de Oliveira (Revista de Letras, 2007)
This essay presents the main aspects related to Wolfgang Iser’s theory of aesthetic effect, through which the author makes a description of the phenomenological process of reading, as far as the reader’s role in literary meaning construction is concerned. In accordance with Iser, the fictional structure of discourse derives from the modification of world’ system of roles, as it is defined by Pragmatics, while the strategies (narrator, fictitious reader, characters, plot) organize the literature’s repertoire (social and literary allusions). On the other hand, the reader is supposed to deal with the textual performance derived from the modified social conventions, by filling up the blanks, going through the experience which results from the äesthetic effect and building the meaning (significance) of the literature.